2017
DOI: 10.1016/j.jmat.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous CDW ground state in Cu2Se: A wave-like fluctuation of the dc I-V curve near 50 K

Abstract: A charge density wave (CDW) ground state is observed in polycrystalline Cu 2 Se below 125 K, which corresponds to an energy gap of 40.9 meV and an electron-phonon coupling constant of 0.6. Due to the polycrystalline structure, the Peierls transition process has been expanded to a wide temperature range from 90 to 160 K. The Hall carrier concentration shows a continuous decrease from 2.1×10 20 to 1.6×10 20 cm -3 in the temperature range from 160 K to 80 K, while almost unchanged above 160 K and below 90 K. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…This gives us a mean-field estimation of the CDW transition temperature (2 = 3.52 T CDW ) to be T CDW ≈ 9.15 K, consistent with the dc measurements. The corresponding coherence length can be estimated to be ξ 0 ≈ 2.4 nm, which is much smaller than the grain ∼1 μm, and similar to the observed value in other polycrystalline samples [31].…”
Section: Resultssupporting
confidence: 85%
“…This gives us a mean-field estimation of the CDW transition temperature (2 = 3.52 T CDW ) to be T CDW ≈ 9.15 K, consistent with the dc measurements. The corresponding coherence length can be estimated to be ξ 0 ≈ 2.4 nm, which is much smaller than the grain ∼1 μm, and similar to the observed value in other polycrystalline samples [31].…”
Section: Resultssupporting
confidence: 85%
“…The increase of Hall carrier density is related with the CDW-like phase transition near 90 K in the electrical resistivity. In general, the CDW formation induces energy band gap opening leading to the decrease of Hall carrier concentration. However, in this case, the Hall carrier densities are increased at the temperatures below the CDW-like phase transition. The broad shoulder in electrical resistivity on the InTe 1−δ compounds is more closely related with the decrease of Hall mobility in the vicinity of the CDW-like phase transition.…”
Section: Resultsmentioning
confidence: 99%
“…The voltage changes linearly with the increase of current at different temperatures, which indicates SnS 2 is a pure metal state under 39.2 GPa. No saturation voltage or regular fluctuation related to charge density waves was found in the differential resistance, d V /d I . , …”
mentioning
confidence: 85%
“…No saturation voltage or regular fluctuation related to charge density waves was found in the differential resistance, dV/dI. 37,38 Pressure-induced metallization or superconductivity is usually accompanied by a collapse or transformation of the crystal structure, and previous Raman and XRD studies have reported that SnS 2 is stable up to 20 GPa. 39−41 High-pressure synchrotron XRD measurements were performed up to 62.7 GPa to verify the structural stability of SnS 2 under higher pressures.…”
mentioning
confidence: 99%